Intercultural Conflict in Groups. Issue 4 (1st October 2016) - Okech, Jane E. Atieno; Pimpleton-Gray, Asher M.; Vannatta, Rachel; Champe, Julia
Abstract : This article provides a critical review of interdisciplinary literature on intercultural conflict management. The authors provide theoretical frameworks and evidence-based strategies to help group counselors more effectively identify and address potential sources of overt and covert intercultural conflict in groups. Using practical examples and integrated case studies, we examine the dynamics of intercultural conflict in groups, effective and ineffective group leader interventions, and implications for research and the practice of group work.